Inexact discretionary inputs in data envelopment analysis - Langroudi, Majid Zerafat Angiz (Springer Berlin Heidelberg, 2013)
In this chapter, the relationship between fuzzy concepts and the efficiency score in Data envelopment analysis (DEA) is dealt with.A new DEA model for handling crisp data using fuzzy concept is proposed.In addition, the relationship between possibility sets and the efficiency score in the traditional crisp CCR model is presented.The relationship provides an alternative perspective of viewing efficiency.With the usage of the appropriate fuzzy and possibility sets to represent certain characteristics of the input data, many DEA models involving input data with various characteristics could be studied.Furthermore, based upon the proposed models, two nondiscretionary models are introduced in which some inputs or outputs, in a fuzzy sense, are inexact discretionary variables.For this purpose, a two-stage algorithm will be presented to treat the DEA model in the presence of an inexact discretionary variable.With this relationship, a new perspective of viewing and exploring other DEA models is now made possible.